2020
DOI: 10.1002/cncr.33104
|View full text |Cite
|
Sign up to set email alerts
|

Differential impact of prognostic parameters in hormone receptor–positive lobular breast cancer

Abstract: BACKGROUND: Invasive lobular breast cancer (BC) is the second most common BC subtype. Prognostic parameters (tumor classification, lymph node status, histologic grade, Oncotype DX recurrence score [RS], progesterone receptor status, and Ki67 index) were retrospectively studied in a large, prospective clinical trial encompassing 2585 patients who had hormone receptor-positive early BC (the West German Study Group PlanB trial). METHODS: BCs were centrally reviewed and classified as lobular (n = 353; 14%) or nonl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 45 publications
(198 reference statements)
4
52
1
Order By: Relevance
“…A comparison of patients with HER2+ ILC and HER2+ IBC-NST provided further evidence that HER2+ ILC has different clinical and biological characteristics [54]: relative to HER2+ IBC-NST, HER2+ ILCs were more often multicentric or multifocal, with a lower histological grade and proliferative index, and show more frequent nodal metastases (i.e. these are similar features observed when ILC is compared to IBC-NST, regardless of HER2 status [15,47,55,56]). Whilst HER2+ ILC and IBC-NST have differing characteristics, both groups appear to benefit similarly from adjuvant treatment with Figure 2 in Sokol et al [40] trastuzumab, with similar recurrence rates, indicating HER2+ ILC patients do benefit from anti-HER2 therapy [54,57].…”
Section: What Is New In Invasive Lobular Carcinoma?mentioning
confidence: 84%
See 1 more Smart Citation
“…A comparison of patients with HER2+ ILC and HER2+ IBC-NST provided further evidence that HER2+ ILC has different clinical and biological characteristics [54]: relative to HER2+ IBC-NST, HER2+ ILCs were more often multicentric or multifocal, with a lower histological grade and proliferative index, and show more frequent nodal metastases (i.e. these are similar features observed when ILC is compared to IBC-NST, regardless of HER2 status [15,47,55,56]). Whilst HER2+ ILC and IBC-NST have differing characteristics, both groups appear to benefit similarly from adjuvant treatment with Figure 2 in Sokol et al [40] trastuzumab, with similar recurrence rates, indicating HER2+ ILC patients do benefit from anti-HER2 therapy [54,57].…”
Section: What Is New In Invasive Lobular Carcinoma?mentioning
confidence: 84%
“…The clinical utility in ILC of the 21-gene OncotypeDx®, remains unclear; two studies show classification of 42% [102] and 35.5% [103] of patients into the intermediate-risk group, which is considered challenging to manage clinically [104]. However, a multivariate analysis of the SEER dataset showed that the OncotypeDx recurrence score was an independent prognostic indicator in ILC [96], and a recent analysis of the PlanB trial data determined that OncotypeDx® classed 72% of ILC as intermediate risk, and 20% and 8% as low and high risk, respectively, amounting to a threefold lower rate of high-risk results compared to non-lobular cancers [55]. These low rates of high-risk ILC are similar to those observed elsewhere [97,98].…”
Section: Molecular Prognosticationmentioning
confidence: 99%
“…The current WHO classification defines ILC as BC composed of dyscohesive cells that are mostly individually dispersed or arranged in single files [19]. However, a large proportion of ILCs does not show this classic growth pattern [43,46,[61][62][63][64][65][66]. In 1975, Fechner reported an ILC variant with solid growth and description of further variants followed [66].…”
Section: Ilc As Carcinoma Growing In Single Filesmentioning
confidence: 99%
“…Furthermore, ILC and BCs of NST constitute a morphological continuum with a proportion of indefinite cases termed mixed BC (NST/ILC) [67]. Mixed BC (NST/ILC) accounts for up to 18% of BC cases (Appendix A, Table A1) [42,61,[67][68][69][70][71]. According to the traditional WHO definition, this term was applicable for BCs showing a mixture of 11-50% ductal and 50-89% lobular growth pattern [72].…”
Section: Ilc As Carcinoma Growing In Single Filesmentioning
confidence: 99%
See 1 more Smart Citation